FORENSIC HISTOLOGICAL ASSESSMENT OF FAT EMBOLISM IN COMBINED INJURY DEATH CASES - Choriev B. A.; Valieva M. T.; Sobirova D. R. (Galaxy International Interdisciplinary Research Journal, 2022)
One of the most common early complications of severe joint injuries is fat embolism. In cases of death due to fat embolism, the final forensic diagnosis of the medical examiner is based on the results of the autopsy and the study of histological examinations. Fat emboli are detected in small blood vessels during histological examination of pieces taken from internal organs (lungs, brain, heart, liver and kidneys).